THE ROLE OF FEED IN POULTRY FARMING (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article discusses the role of feed in poultry farming and its effects on the poultry organism. In modern poultry farming, preparing a proper and balanced feed ration is an important factor in achieving high productivity, maintaining poultry health, and increasing economic efficiency.